Alcohol consumption and breast cancer risk among women from five ethnic groups with light to moderate intakes: The Multiethnic Cohort Study. Issue 6 (9th October 2013) - Park, Song‐Yi; Kolonel, Laurence N.; Lim, Unhee; White, Kami K.; Henderson, Brian E.; Wilkens, Lynne R.
<x xml:space="preserve">Abstract</x> Higher alcohol consumption, even at moderate levels, has been associated with an increased risk of breast cancer in epidemiological studies. However, prior studies were conducted in mostly white populations. To assess the relationship of alcohol consumption to postmenopausal breast cancer risk in a multiethnic population of largely never, light or moderate drinkers, we prospectively examined the association in 85, 089 women enrolled in the Multiethnic Cohort in Hawaii and California. During a mean follow‐up of 12.4 years, 3, 885 incident invasive breast cancer cases were identified. Hazard ratios (HRs) and 95% confidence intervals (CIs) were estimated using Cox proportional hazard models, controlling for potential confounders. Higher alcohol consumption was associated with increased risk of breast cancer: compared to nondrinkers, HRs were 1.23 (95% CI: 1.06–1.42), 1.21 (95% CI: 1.00–1.45), 1.12 (95% CI: 0.95–1.31) and 1.53 (95% CI: 1.32–1.77) for 5–9.9, 10–14.9, 15–29.9 and ≥30 g/day of alcohol, respectively. The positive association was seen in African American, Japanese American, Latino and white, but not in Native Hawaiian women, and in those with tumors that were both positive and negative for estrogen and progesterone receptors (ER/PR). This prospective study supports previous findings that light to moderate alcohol consumption increases breast cancer risk, and demonstrates this association in several ethnic groups besides whites, independent of ER/PR status.